Transparansi dan Akuntabilitas Laporan Kegiatan Organisasi Mahasiswa: Studi Kualitatif: Transparency and Accountability of Student Organization Activity Reports: A Qualitative Study - Azis, Ismi; Selviani, Ayudho; Suryani, Mardian (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to examine the transparency and accountability of activity reports (LPJ) prepared by student organizations (ORMAWA) at the Nahdlatul Ulama College of Islamic Economics (STIESNU) Bengkulu. Design/Methodology/Approach: This research employs a qualitative approach, with data collected through direct observation, in-depth interviews, and document analysis. Findings: Most student organizations prepare accountability reports as a formal form of responsibility; however, weaknesses were found in the transparency of financial information and accountability for the use of activity funds. Research Implications: To ensure that all student organization activities are conducted more fairly and transparently, the campus should provide regular training and intensive guidance for student organizations at STIESNU Bengkulu.